2010
DOI: 10.2174/092986710792927796
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorins and their Receptors in Stem and Cancer Cells

Abstract: There is a growing body of evidence that links cancer with genes and pathways that are required for normal embryonic development, increasing the possibility that cancer cells with stem cell properties, particularly self-renewal and multipotentiality, are primarily involved in tumor formation and progression. One novel pathway that is important in regulating the morphogenesis, proliferation, survival and growth in a variety of adult and embryonic tissues is the semaphoring signaling pathway. Semaphorins are a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 106 publications
0
5
0
Order By: Relevance
“…CRMP2 binds to tubulin and promotes microtubulin assembly. Class 3 semaphorins are secreted proteins that alter the cytoskeleton and organization of actin filaments and microtubules and play a role in tumor formation or prevention …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CRMP2 binds to tubulin and promotes microtubulin assembly. Class 3 semaphorins are secreted proteins that alter the cytoskeleton and organization of actin filaments and microtubules and play a role in tumor formation or prevention …”
Section: Discussionmentioning
confidence: 99%
“…Class 3 semaphorins are secreted proteins that alter the cytoskeleton and organization of actin filaments and microtubules and play a role in tumor formation or prevention. 40 Cigarette smoke increases ERK1/2 phosphorylation in airway lining cells and alveolar macrophages in mice exposed for 10 days and 6 months. 41 ERK1/2 also significantly increases in lung tissues from emphysema patients compared to controls.…”
Section: Smoke-affected Lung Proteinsmentioning
confidence: 99%
“…Many recent reports have revealed that axon guidance cue molecules like the semaphorin /plexin axis are hijacked by different cancer cells to aid in their growth, differentiation, and renewal of cancer stem-like cells [31][32][33][34]. Our interest in investigating the role of Plexin-B3 in stem cell properties of PC cells came from various studies that demonstrate Plexin-B's role in regulating the stemness of different cancers [30,[35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated the requirement for CD100 in the induction of antigen-specific T cells and the maturation of DCs (Kumanogoh et al, 2002). Recent study showed that semaphorins and their receptors were primarily involved in tumor formation and progression (Micucci et al, 2010). However, the expression of Plexin-B1 by gliomas and its relationship with the pathological progression of this tumor type remain unclear.…”
Section: Introductionmentioning
confidence: 99%